Prevalence of Intestinal Parasitic Infections Among Children in Selected Communities of Ifo Local Government Area (LGA) of Ogun State, Nigeria - T.O.O, Uthman; T.O.S, Adewoga; F.M., Banjo; A.A.R. , Adebambo; M.T., Okeowo, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Intestinal parasitic infections are diseases of major public health importance caused by nematodes and protozoans. Developing countries are the most affected as the infections are associated with poverty. This study was conducted to determine the prevalence of intestinal parasitic infections among children in selected communities of Ifo Local Government Area (LGA) of Ogun State, Nigeria. A total of two hundred and seventy-four (274) feacal samples were collected from children between the ages of 4 and 15 selected randomly in the communities for the study. The faecal samples were examined for presence of parasites using the formaldehyde-ether concentration technique. Eighty-four (30.66%) of the feacal samples were positive for one intestinal parasites infection or the other. Mixed infection was observed in 22 (8.03%). Ascaris lumbricoides was the most prevalent, followed by Hookworm (5.47%). While Trichuris trichiura was the least prevalent. Highest prevalence was recorded in Adenrele community (30.56%), while the least prevalence was recorded in Solu community (27.08%). There was no significant difference (p>0.05) between the infection rate of the helminth parasites found in the area. Highest prevalence was observed in the female gender, 18.61% and the 7-9 years age group, 11.68%. The study showed that intestinal parasitic infection is prevalent among children in the various communities in Ifo Local Government Area and the infection is predominant among young female children. Continuous deworming exercise, public enlightenment good hygiene practices will reduce the incidence of parasitic infections among children in area.